2014
DOI: 10.1186/1556-276x-9-658
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement of ITO/oxide/semiconductor MOS-structure silicon solar cells with voltage biasing

Abstract: In this study, we demonstrate the photovoltaic performance enhancement of a p-n junction silicon solar cell using a transparent-antireflective ITO/oxide film deposited on the spacing of the front-side finger electrodes and with a DC voltage applied on the ITO-electrode. The depletion width of the p-n junction under the ITO-electrode was induced and extended while the absorbed volume and built-in electric field were also increased when the biasing voltage was increased. The photocurrent and conversion efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The Q vol value is also dependent on the UV intensity, since stronger intensity induces more negative O 2 – radicals (Figure S6). Therefore, this photoinduced electric field can be modulated by UV, similarly working in the solar cells with the bias voltage …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Q vol value is also dependent on the UV intensity, since stronger intensity induces more negative O 2 – radicals (Figure S6). Therefore, this photoinduced electric field can be modulated by UV, similarly working in the solar cells with the bias voltage …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this photoinduced electric field can be modulated by UV, similarly working in the solar cells with the bias voltage. 34 To assess this photoinduced field-effect passivation, τ n of silicon coated with the various layers as functions of UV irradiation duration and intensity were measured systematically, as shown in Figure 4. Under UV soaking, the τ n of silicon deposited by PEDOT:PSS, PEDOT:PSS/PDMS, and PE-DOT:PSS/TiO 2 layers is not changed at all.…”
Section: Resultsmentioning
confidence: 99%
“…Efficiency can also be increased using inversion-layer metal-insulator-semiconductors (IL-MIS) and metal-oxide-semiconductors (MOS) [ 15 , 16 , 17 , 18 , 19 ]. Researchers have reported that the photovoltaic performance of MIS or MOS solar cells (SC) can be enhanced through the application of bias voltage [ 20 , 21 , 22 ]; however, few studies have examined the effects of plasmonic metallic nanoparticles in conjunction with bias voltage on MOS solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…3 ). Therefore, BSO demonstrates a realistic potential to replace traditional transparent conductive oxides, such as indium-based systems 4 , in optoelectronic technology. Furthermore, both BSO and SSO in thin film form show further improvement in light transparency, electrical conductivity 5,6 , and electron mobility compared to the bulk compounds, which is generally attributed to a low electroneffective mass in the range of 0.2-0.4 m e [7][8][9][10][11] .…”
mentioning
confidence: 99%
“…Fig 4. Comparison of the calculated electronic structure of BaSnO 3 slab with different terminations.…”
mentioning
confidence: 99%